1994
DOI: 10.1111/j.1439-0442.1994.tb00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Levels of the Prostaglandin F Metabolite during the Postpartum Period in Bos indicus Cows in the Humid Tropics

Abstract: Summary Plasma levels of the prostaglandin F2α metabolite (15‐ketodihydroprostaglandin F2α) were determined by radioimmunoassay in 26 postpartum multiparous Brahman cows. Variation in the concentrations of the metabolite was high among animals. 15‐Ketodihydro‐PGF2α concentrations on day 0, 5, 10, 15 and 20 postpartum ranged from 402 to ≥1000, from 251 to ≥1000, from 237 to ≥1000, from 75 to 608 and from 75 to 267 pmol l−1, respectively. The prostaglandin metabolite levels were elevated at parturition and remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
1
3
0
1
Order By: Relevance
“…The observed trend of changes in PGFM values was found to be similar to the findings of Thompson et al (1987), Toribio et al (1994) and Dhami et al (2017), who all reported that the PGFM levels in the prepartum days were low, but increased many fold around parturition. The levels thereafter came back to normal within 20-30 days postpartum.…”
Section: Plasma Cortisolsupporting
confidence: 87%
“…The observed trend of changes in PGFM values was found to be similar to the findings of Thompson et al (1987), Toribio et al (1994) and Dhami et al (2017), who all reported that the PGFM levels in the prepartum days were low, but increased many fold around parturition. The levels thereafter came back to normal within 20-30 days postpartum.…”
Section: Plasma Cortisolsupporting
confidence: 87%
“…La determinación de P4 se realizó en la Facultad de Ciencias Veterinarias (UNCPBA, Tandil, Buenos Aires). Se utilizó un kit para RIA (COAT A COUNT, Siemens Healthcare Diagnostic Inc., CA, USA) previamente validado para bovinos 14 . El coeficiente de variación intra-ensayo fue < 7% para concentraciones entre 0,1 y 40 ng/ml y el inter-ensayo fue < 3,5%.…”
Section: Determinación De Progesteronaunclassified
“…Plasma samples were assayed at the Facultad de Ciencias Veterinarias, U.N.C.P.B.A., Tandil, Argentina. Samples were analyzed using a progesterone RIA kit (COAT A COUNT, Siemens Healthcare Diagnostic Inc., CA, USA) previously validated for use with bovine plasma (Toribio et al, 1994). The intra-assay coefficient of variation was less than 7% for concentrations between 0.1 and 40 ng/mL, the interassay coefficient of variation was less than 3.5% and assay sensitivity was 0.01 ng/mL.…”
Section: Blood Collection and Radioimmunoassay (Ria)mentioning
confidence: 99%